Protective effects of melatonin and vitamin E in brain damage due to gamma radiation - An experimental study - Erol, FS; Topsakal, C; Ozveren, MF; Kaplan, M; Ilhan, N; Ozercan, IH; Yildiz, OG (Springer, 2004)
Gamma radiation is known to cause serious damage in the brain, and many agents have been used for neuroprotection. In this study, lipid peroxidation levels and histopathological changes in brain tissues of whole-body irradiated rats with likely radiation injury were compared to those with melatonin and vitamin E protection. Forty rats in four equal groups were used. The control group received neither radiation nor medication. The remaining groups received doses of 720 cGy in two equal fractions 12 h apart. The second group received radiation but no medication, the third received radiation plus 100 mg/kg per day of vitamin E i.p., and the fourth received radiation plus 100 mg/kg per day of melatonin i.p. over 5 days. On the 10th postoperative day, all the rats were decapitated and specimens from parietal cortices were analyzed for tissue malondialdehyde (MDA) levels and histopathological changes. Increases in MDA were relatively well prevented by melatonin treatment but less so with vitamin E therapy. On histopathological examination, melatonin significantly reduced the rates of edema, necrosis, and neuronal degeneration, whereas vitamin E reduced only necrosis. Neither substance was capable of preventing vasodilatation. In conclusion, melatonin may be useful in preventing the pathological changes of secondary brain damage as a result of free oxygen radicals generated by irradiation.
Keywords: cortex; gamma radiation; lipid peroxidation; malondialdehyde; melatonin; vitamin E